2001
DOI: 10.1021/ol007047+
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Transformations on d-Glucose-Derived Eight-Membered Ring Carbocycles

Abstract: [structure: see text]. The cyclooctenol derivative 1 can be transformed into the nine-membered ring lactone 3, as well as the amino-containing carbocycles 4 and 5. The corresponding ketone 2 gives access to the conformationally locked azasugar 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 20 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…van Boom and co-workers reported a 1,3-diaxial NOE interaction between 1-H and 7-H in a corresponding derivative, however, we could not verify this. [22] An Xray analysis of a closely related compound confirmed the equatorial orientation of the newly generated hydroxy function after the TIBAL-promoted Claisen rearrangement. [23] Epoxidation with m-chloroperbenzoic acid (MCPBA) and cyclopropanation with the Simmons-Smith reaction [24] (Furukawa modification [25] ) of the functionalized cyclooctenone derivative 26 furnished the optically pure diastereomers 27 and 28, respectively.…”
Section: Resultsmentioning
confidence: 85%
“…van Boom and co-workers reported a 1,3-diaxial NOE interaction between 1-H and 7-H in a corresponding derivative, however, we could not verify this. [22] An Xray analysis of a closely related compound confirmed the equatorial orientation of the newly generated hydroxy function after the TIBAL-promoted Claisen rearrangement. [23] Epoxidation with m-chloroperbenzoic acid (MCPBA) and cyclopropanation with the Simmons-Smith reaction [24] (Furukawa modification [25] ) of the functionalized cyclooctenone derivative 26 furnished the optically pure diastereomers 27 and 28, respectively.…”
Section: Resultsmentioning
confidence: 85%
“…Further reductions in catalyst loading were not explored. Scheme 2 ignores irreversible cross metathesis reactions, because we observed no evidence for heterodimeric products at 0.01 M. ‡ Crystallographic data for 16b:C 13 The results in Table 1 also suggest the presence of a modest (less than five-fold) Thorpe-Ingold effect. 26 Murphy and coworkers 27 proposed that a single methyl group placed appropriately could increase RCM yields dramatically; the effect is considerably less clear cut in our system.…”
Section: Synthetic Studiesmentioning
confidence: 81%
“… Synthesis of 5-(tert-butyldimethylsilyloxy)-2-(phenylmethoxy)-hex-2-enal ( 4 ). In 2001, van Boom et al examined the transformations of D-glucose-derived eight-membered ring carbocycle 5 [ 20 ]. It was found that multistage process involved the formation of densely functional 2-benzyloxysubstituted 2-alkenals 9 ( Scheme 2 ) via a side reaction.…”
Section: Synthesis Of α-Functionally Substituted αβ-Unsaturated Aldehydesmentioning
confidence: 99%